Materials Processing and Crystal Growth for Thermoelectrics (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This volume contains recent developments in the field of thermoelectric with a focus on materials research, including inorganic, polymer and composite materials as well as different approaches to materials processing. These studies are representative of some of the continuing technological development in the field of thermoelectrics.